RELATIONSHIP BETWEEN INDIVIDUAL CHARACTERISTICS WITH SYMPTOMS OF LOWER BACK PAIN IN PUTRI DAFFA CONVECTION WORKERS IN DEPOK, 2023 - Hanifah Fauziah Suhendra; Dihartawan (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Low back pain is a very common problem in people of all ages and is generally described as pain, muscle tension, or stiffness located below the costal margin and above the lower gluteal fold, with or without pain in the legs. This research is a descriptive analytical study using a cross-sectional approach. This research was conducted at the Putri Daffa Convection located in Limo District, Depok with a sample of 70 female employees of the Daffa Convection. The data collection tool uses a questionnaire. The results of the Chi-square test analysis and simple logistic regression on the variable length of work showed that there was no significant relationship between work experience and low back pain, there was no relationship between work experience and low back pain, there was a relationship between work posture and low back pain, and there was no The relationship between age and low back pain. From the results of this research, it is necessary to have ways to prevent low back pain and ways to reduce pain if low back pain occurs, namely daily back exercises, being careful when working, protecting your back when sitting and standing and staying active and living a healthy life.